PENINGKATAN MINAT DAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN CANVA INTERAKTIF BAGI SISWA KELAS XII-IPA-7 SMA NEGERI 5 BALIKPAPAN - Dwi Suryani (Melati Institute, 2023)
This Classroom Action Research (PTK) has a core problem of teacher anxiety towards students in learning Mathematics after the Covid-19 pandemic. Learning behavior is very concerning, namely lack of discipline, slow to respond, lack of concern for initiative in learning. Understanding the concept of low Mathematics content. Through in-depth observation and comparison with literature reviews from journals, researchers offer solutions in the form of Project Based Learning (PJBL) learning models and interactive media as answers to solving current Mathematics learning problems. PTK has objectives, namely; (1) increasing interest in learning (2) Mathematics learning outcomes for students using the PJBL Model and interactive Canva Media in Class XII-IPA 7 at SMA Negeri 5 Balikpapan. (2) This PTK research method uses 2 cycles of cycle procedures. Each cycle consists of 4 (four) steps namely planning, implementation, observation and reflection. The data were obtained from the observation instrument entries by the observer and the results of the evaluation. The results of the filling in the interest in learning cycle I and the cycle showed an increase of the score: (61). interest increases to a score: (69.5) there is an increase in interest in the score: (8.5). The increase in Mathematics learning outcomes in Cycle I obtained an average score of: 71.8 and in Cycle II an average of: 78 there was an increase (6.2.) The conclusion shows that the interactive PJBL and Canva models can increase interest and learning outcomes, interest in encourage a fun learning atmosphere and learning experience will increase as the learning process focuses on students.